Primary cilia: a novel research approach to overcome anticancer drug resistance - Lee, Kyung Ho (Frontiers in Molecular Biosciences, 2023)
Primary cilia are cellular organelles that consist of a microtubule skeleton surrounded by a membrane filled with cell signaling receptors. Many studies have shown that primary cilia are cellular antennas, which serve as signaling hubs and their assembly and disassembly are dynamically regulated throughout the cell cycle, playing an important role in regulating cellular homeostasis. Aberrant control of primary cilia dynamics causes a number of genetic disorders known as ciliopathies and is closely associated with tumorigenesis. Anticancer drug resistance is a primary cause of chemotherapy failure, although there is no apparent remedy. The recent identification of a relationship between anticancer drug resistance and primary ciliary dynamics has made primary cilia an important target subcellular organelle for overcoming anticancer drug resistance. Therefore, the research on primary ciliary dynamics may provide new strategies to overcome anticancer drug resistance, which is urgently needed. This review aims to summarize research on the relevance of primary cilia and anticancer drug resistance, as well as future possibilities for research on overcoming anticancer drug resistance utilizing primary cilia dynamics.